PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL DALAM PEMBELAJARAN PAI - Ida Fitriana; Fitriyani Kosasih; Elih Herliati; Jejen Ramdani; Lia Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology in the era of the Fourth Industrial Revolution and Society 5.0 has brought significant changes to the world of education, including in the teaching of Islamic Religious Education (IRE). This study aims to analyze the concepts, principles, characteristics, types, and relevance of developing digital learning media in improving the quality of IRE instruction. The method used is library research with a qualitative approach through the analysis of various relevant scientific literature sources, such as journals, books, and previous research findings. The data analysis technique employs content analysis through the stages of data reduction, data presentation, and drawing conclusions. Research findings indicate that digital learning media in Islamic Education (PAI) are information technology-based tools capable of enhancing student interactivity, motivation, and comprehension. The development of effective media must adhere to the principles of relevance, effectiveness, efficiency, appeal, and the integration of Islamic values. Various types of media, such as audio, visual, audiovisual, e-learning, and interactive media, have been shown to contribute positively to the learning process. However, their implementation still faces challenges in the form of limited infrastructure, teachers’ digital competencies, and ethical aspects of technology use. Thus, the development of digital learning media is highly relevant to improving the quality of PAI learning to make it more interactive, contextual, and meaningful, as well as capable of supporting the character development of students in the digital age. Keywords: Digital Learning Media, Islamic Religious Education, Educational Technology, Interactive Learning.